2004
DOI: 10.15517/rfl.v30i2.4442
|View full text |Cite
|
Sign up to set email alerts
|

Variación morfosintáctica y enseñanza del español como lengua extranjera: reflexiones de un lingüista metido a profesor

Abstract: RESUMENEn este trabajo se realiza un examen crítico del tratamiento de la variación morfosintáctica de la lengua española en los libros de texto para su enseñanza como lengua extranjera. El propósito principal es elaborar algunos comentarios generales sobre la necesidad de considerar la heterogeneidad idiomática en las clases. Palabras clave: Variación morfosintáctica, enseñanza, español como segunda lengua. ABSTRACTIn this paper a critical revision about Spanish language morphosyntactic variation treatment is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 3 publications
1
6
0
2
Order By: Relevance
“…This may be in part because most lower‐level textbooks do not address regional variation effectively or at all. Textbook surveys have shown that most textbooks opt for oversimplified explanations and avoid drawing connections between the forms or vocabulary they present and the regional varieties where they are used (Gilmore, ; Sánchez‐Avendaño, ; Wieczorek, , ). For instance, most surveys have noted that textbooks almost always include instruction on the vosotros (second‐person plural) forms used in Spain but rarely mention voseo (the use of vos as a second‐person singular pronoun), which is used in multiple areas of South America (see Schmidt‐Rinehart & Leloup, this issue).…”
Section: Review Of Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…This may be in part because most lower‐level textbooks do not address regional variation effectively or at all. Textbook surveys have shown that most textbooks opt for oversimplified explanations and avoid drawing connections between the forms or vocabulary they present and the regional varieties where they are used (Gilmore, ; Sánchez‐Avendaño, ; Wieczorek, , ). For instance, most surveys have noted that textbooks almost always include instruction on the vosotros (second‐person plural) forms used in Spain but rarely mention voseo (the use of vos as a second‐person singular pronoun), which is used in multiple areas of South America (see Schmidt‐Rinehart & Leloup, this issue).…”
Section: Review Of Literaturementioning
confidence: 99%
“…Many language learners struggle to understand novel speakers in their second language (L2). While this may be the result of insufficient listening practice, another explanation could be students' limited knowledge of L2 regional variation: Previous research has shown that regional variation is rarely discussed either in introductory language textbooks or by instructors (Gallego & Conley, ; Gilmore, ; Sánchez‐Avendaño, ; Wieczorek, , ). Since learners have been shown to be capable of recognizing certain L2 dialects at rates above chance (Clopper & Bradlow, ; Cunningham‐Andersson, ; Stephan, ; Sullivan & Karst, ) and since dialect familiarity has been shown to help learners' comprehension of native speech (Matsuura, Chiba, & Fujieda, ; Schmidt, ), it is unclear to what extent exposure, with or without direct instruction, impacts learners' concept and development of dialect in the L2.…”
Section: Introductionmentioning
confidence: 99%
“…The recommendation to incorporate this additional material into an already overloaded Spanish curriculum in general has met with resistance on several fronts (Long, 2011). In contrast, it has also been recommended that the voseo be included in one fashion or another (Cameron, 2012(Cameron, , 2014Congosto Mart ın, 2004;Lotherington, 2007;Mason & Nicely, 1995;Pearson, 2006;S anchez Avendaño, 2004;Shenk, 2014;Watts, 2001). The case for inclusion of the voseo in the Spanish curriculum of the United States can be made on many fronts.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Presently, most if not all Spanish textbooks used in the United States incorporate the form of vosotros, indisputably present in Spain with a population of 48 million Spanish-speakers. Nevertheless, regular users of the voseo in Latin America number more than 85 million -a dramatically larger number in comparison (Mason & Nicely, 1995;Potowski, 2010)-yet this structural paradigm is omitted from nearly all Spanish textbooks that are used in the United States (Cameron, 2012(Cameron, , 2014Lotherington, 2007;Mason & Nicely, 1995;S anchez Avendaño, 2004;Shenk, 2014;Watts, 2001). Germane to this study, the presence of the voseo is very noticeable in Costa Rica, in contrast with the relative absence of the tuteo, a form that is ubiquitous in commonly used Spanish instructional materials (Cabal Jim enez, 2013;Cameron, 2012Cameron, , 2014Jara Murillo, 2008;Kapovi c, 2007;Moser, 2006Moser, , 2008Vargas Dengo, 1974;Villegas, 1963).…”
Section: Review Of Literaturementioning
confidence: 99%
See 1 more Smart Citation